Hate speech in adolescents: A binational study on prevalence and demographic differences - Castellanos, Melisa; Wettstein, Alexander; Wachs, Sebastian; Kansok-Dusche, Julia; Ballaschk, Cindy; Krause, Norman; Bilz, Ludwig (Frontiers in Education, 2023)
Hate speech, or intentional derogatory expressions about people based on assigned group characteristics, has been studied primarily in online contexts. Less is known about the occurrence of this phenomenon in schools. As it has negative consequences for victims, perpetrators, and those who witness it, it is crucial to characterize the occurrence of offline (i.e., in the school) and online hate speech to describe similarities and differences between these two socialization contexts. The present study aimed to investigate the prevalence of hate speech witnessing, victimization, and perpetration, in a sample of 3,620 7th to 9th graders (51% self-identified as female) from 42 schools in Germany and Switzerland. We found that 67% of the students witnessed hate speech in their school, and 65% witnessed online hate speech at least once in the past twelve months. Approximately 21% of the students self-identified as offline perpetrators and 33% as offline victims, whereas these percentages were lower for online hate speech (13% and 20%, respectively). In both settings, skin color and origin were the most common group references for hate speech (50% offline and 63% online). Offline hate speech mainly came from classmates (88%), unknown sources (e.g., graffiti; 19%), or teachers (12%), whereas online hate speech mostly came from unknown persons (77%). The most frequent forms of offline hate speech were offensive jokes (94%) and the spread of lies and rumors about the members of a specific social group (84%). Significant differences by country, gender, and migration background were observed. Girls reported more offline victimization experiences, less perpetration, and a greater frequency of witnessing hate speech. This difference was larger in magnitude in the online setting. Students in Switzerland reported being exposed to hate speech more often than students in Germany. Students with a migration background reported higher hate speech victimization based on skin color and origin than students without a migration background. The high prevalence of hate speech highlights the need for school-based prevention programs. Our findings are discussed in terms of the practical implications.